How does the U.S. Government violate the infant formula marketing code? - George Kent (World Nutrition, 2023)
The United States’ Special Supplemental Nutrition Program for Women, Infants, and Children, commonly known as WIC, is based in the United States Department of Agriculture (USDA). It provides services to about half the infants born in the country, with many of them getting subsidized infant formula. WIC manages this in close collaboration with major manufacturers of formula. This commentary examines WIC’s practices in relation to the International Code of Marketing of Breastmilk Substitutes and concludes that the United States is a major violator of the aims and principles of the Code.